Integrating Islamic Principles with Modern Criminal Justice: Re-Evaluating Hudud Laws in the Context of Digital Evidence and Procedural Fairness - Haider Mahmood Jawad (Qiyam Islamic Studies Center Foundation, 2025)
The rapid adoption of digital forensics in Muslim jurisdictions poses doctrinal and procedural dilemmas for the enforcement of hudud, the fixed punishments regulated by Islamic criminal law. Although classical jurists demanded near-absolute certainty, statutes now admit blockchain logs, DNA profiles, and geolocation data whose epistemic status is contested. This study investigates whether authenticated digital evidence, evaluated through a maqāṣid-aligned reliability matrix, preserves both procedural fairness and the deterrent mission of hudud. A convergent mixed-methods design combined doctrinal analysis with empirical testing of 210 criminal case files from Malaysia, Aceh, and Saudi Arabia (2015-2024). Reliability indices were computed for five evidence types; Bayesian updating estimated posterior guilt probabilities; interviews with 67 justice actors contextualised findings; cost–benefit metrics assessed restorative settlements. DNA profiles (mean RI = 0.91) and blockchain logs (0.87) achieved high evidentiary reliability, producing shubha deflection rates below 10 %. Geolocation data (0.74) and digital confessions (0.79) generated significantly higher doubt and conversion to taʿzīr. Restorative settlements delivered cost–benefit ratios above 1.1 and victim-satisfaction scores exceeding 78/100, particularly in Aceh, were digital monitoring enhanced compliance. Jurisdictions employing multidisciplinary verification panels recorded wrongful-conviction reversals below 4 %. The findings demonstrate that modern forensic artefacts can coexist with classical proof doctrines when governed by transparent authentication and probabilistic evaluation. Implementing a maqāṣid-based reliability matrix offers courts a principled route to align divine mandates, technological progress, and human-rights safeguards, thereby modernising Islamic criminal justice without compromising its ethical foundations, in diverse contexts worldwide.